THE IMPORTANCE OF TEACHER AND PARENT COLLABORATION IN SUPPORTING CHILDREN'S LEARNING - Habibullah, Moh; Ulum, Mohammad Bahrul; Maulana, Zaki (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
A harmonious relationship between teachers and parents plays an important role in supporting children's learning process. This article examines the benefits of collaboration between the two parties in increasing children's learning motivation, academic achievement and emotional development. This research uses a qualitative approach with analysis based on literature review and in-depth interviews to understand the dynamics of this collaboration. The research results show that regular and effective communication between teachers and parents is able to create a conducive learning environment, both at school and at home. This support has a positive impact on children, including increasing their self-confidence and involvement in the learning process. Apart from that, understanding the roles of teachers and parents and using technology to bridge communication has proven to be an important strategy in facing various challenges, such as limited time and facilities. This article provides practical recommendations for strengthening collaborative relationships between teachers and parents.